Clinical Determinants of Disease Progression in Patients With Beta-Sarcoglycan Gene Mutations - Marchetti, Giulia Bruna; Valenti, Luca; Torrente, Yvan (Frontiers in Neurology, 2021)
Background: Limb Girdle Muscular Dystrophy 2E (LGMD 2E), recently renamed as autosomal recessive limb-girdle muscular dystrophy-4 (LGMDR4), is characterized by the lack of beta-sarcoglycan, normally expressed in skeletal muscles and cardiomyocytes. We hypothesized that progressive respiratory and left ventricular (LV) failure in LGMDR4 could be associated to the age and interrelated phenomena of disease’s natural history. Methods: We conducted a retrospective review of the records of 26 patients with LGMDR4. Our primary objective was to compare the rates of decline among creatine phosphokinase (CPK) values, pulmonary function test (PFT) measures, and echocardiographic estimates and to relate them to patients’ age. Results: The rates of decline/year of CPK, PFTs and LV function estimates are significatively bound to age, with the LV ejection fraction (EF) being the strongest independent variable describing disease progression. Moreover, the rate of decline of CPK, PFTs and LV differed in patients grouped according to their genetic mutations, demonstrating a possible genotype-phenotype correlation. The parallel trend of decline in CPK, PFTs and EF values demonstrates the presence in LGMDR4 of a simultaneous and progressive deterioration in muscular, respiratory, and cardiac function. Conclusions: This study expands the current knowledge regarding the trend of CPK values and cardiac and respiratory impairment in patients with LGMDR4, to optimize the monitoring of these patients, to improve their quality of life and provide clinical indices capable of quantifying the effects of any new gene or drug therapy.